2020
DOI: 10.1186/s12889-020-08607-7
|View full text |Cite
|
Sign up to set email alerts
|

Integration of a Kalman filter in the geographically weighted regression for modeling the transmission of hand, foot and mouth disease

Abstract: Background: Hand, foot and mouth disease (HFMD) is a common infectious disease whose mechanism of transmission continues to remain a puzzle for researchers. The measurement and prediction of the HFMD incidence can be combined to improve the estimation accuracy, and provide a novel perspective to explore the spatiotemporal patterns and determinant factors of an HFMD epidemic. Methods: In this study, we collected weekly HFMD incidence reports for a total of 138 districts in Shandong province, China, from May 200… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…Moreover, compared with population density and GDP per capita, hospital beds per 10,000 persons ha a greater explanatory power for HFMD incidence. The result is consistent with the findings in Shandong Province [ 23 ]. It suggests that the healthcare level may play an essential role in controlling the spread of HFMD.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, compared with population density and GDP per capita, hospital beds per 10,000 persons ha a greater explanatory power for HFMD incidence. The result is consistent with the findings in Shandong Province [ 23 ]. It suggests that the healthcare level may play an essential role in controlling the spread of HFMD.…”
Section: Discussionsupporting
confidence: 93%
“…Most of the studies were conducted in a single province or local area, while the influence of meteorological and socioeconomic factors is more complex in the vast area of mainland China. In addition, a study found that the number of hospital beds per capita was also one of the dominant determinants that influence HFMD incidence in Shandong [ 23 ]. The number of hospital beds per capita and the number of health technicians per capita are critical indicators to measure the health resources of a region, but most studies ignored the influence of this factor.…”
Section: Introductionmentioning
confidence: 99%
“…This is a major challenge because the available data are very sparse and noisy, and the parametric form of transmission rates is also unknown. By assimilating data across multiple geographic regions and coupling public data with a dynamic mechanistic model, smooth transmission rates can be estimated using a Kalman filter approach (32; 33) – as already used in epidemiology for COVID-19 spread (34; 35; 36) or for other epidemics with regional variability (37). More specifically, we develop a sophisticated method to address this difficult problem based on two important methodological innovations: (1) in the model with the introduction of time-varying dynamics for the transmission rate, including a Wiener process that accounts for modeling errors, and (2) in the way the population is integrated, as we use a new method from the Kalman filter that is compatible with population approaches.…”
Section: Introductionmentioning
confidence: 99%
“…It explores the spatial changes and related driving factors of the research object in a certain scale by establishing a local regression equation of each point in the spatial range. GWR has been utilized to understand how spatial determinants vary across space in health and diseaserelated researches, such as targeting the spatial context of obesity determinants (Oshan et al 2020) and modeling the transmission of hand, foot, and mouth disease (Hu et al 2020). Some of the research work also focused on using GWR in modeling diabetes and heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…While much literature focuses on the applications of GWR in diabetes and heart disease (Hu et al, 2020), none studied the spatiotemporal variation of leading factors that may cause the diseases. Furthermore, the traditional GWR method assumes that all of the regression processes are in the same spatial scale, constraining local relationships within each model to vary at the same spatial scale (Yang 2014).…”
Section: Introductionmentioning
confidence: 99%